Analisis Perkembangan Ekonomi di Era Revolusi Indrustri 4.0 Dan 5.0 dalam Merekonstruksi Kepribadian Islam Untuk Mengurangi Krisis Moral (Lost Of Adab) - Elvan Tedio Fawaz; Ahta Abdul Mursyid Husni Mubarok; Muhammad Azka Maulana (Edumedia Solution, 2022)
Discussing the importance of morals or etiquette in the era of the industrial revolution 4.0 and 5.0 is an interesting issue to follow. The interesting thing is that the increasingly sophisticated technological advances are not necessarily able to maintain the moral personality of mankind, as evidenced by the start of the development of the industrial world, it has not guaranteed a good human civilization and morals, and is also strengthened by the emergence of various kinds of news of crime, violence, sexual deviations, and so on. rampant where a person can not speak well and easily do bad things that make a loss of adab today brings such a bad impact for future generations. So we need a solution idea to answer this problem. This study has the following objectives: 1) to determine economic progress in the post-pandemic era of the industrial revolution 4.0 and 5.0; 2) to find out the benefits of economic and technological development to ensure a civilized and moral human being. This research is qualitative, using data and literature review which is strengthened by analysis from various sources who experience economic problems. The collected data was then analyzed by descriptive analysis method. By analyzing post-pandemic economic developments and the entry of the technological development revolution era towards 5.0, it will form an identity for every Muslim to re-maintain their Shibghoh as a religious community. In fact, with this research, the author finds that with the development of the economy and the industrial revolution, it is also obligatory to develop morals and etiquette of a religious community, because the position of adab and morals will not be replaced by the position of progress today. The author hopes that the current economic development and industrial revolution can maintain the sibghoh adab and morals of mankind.